2021
DOI: 10.16920/jeet/2021/v34i0/157158
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Mediated Higher Education Provision during the COVID-19 Pandemic: A Qualitative Assessment of Engineering Student Experiences and Sentiments

Abstract: The advent of COVID-19 at the beginning of 2020 put universities worldwide into one of the most significant educational disruptions ever experienced. The unrelenting pandemic forced universities to turn to technology to ensure continuity of education. This abruptly changed learning modes for students, with potential implications on the quality of education and the student experience. Therefore, it became necessary to study experiences and sentiments toward learning under the pandemic through the lens of studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 13 publications
4
30
0
3
Order By: Relevance
“…e finding is in harmony with previous studies in flipped classrooms [6,8,10,12,14], which confirmed that flipped classroom can enhance language learning in various domains and improve vocabulary acquisition. In addition, these researchers believed that flipped classrooms facilitate learning in an innovative way especially in this technology era.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…e finding is in harmony with previous studies in flipped classrooms [6,8,10,12,14], which confirmed that flipped classroom can enhance language learning in various domains and improve vocabulary acquisition. In addition, these researchers believed that flipped classrooms facilitate learning in an innovative way especially in this technology era.…”
Section: Discussionsupporting
confidence: 90%
“…Teachers tried to incorporate digital literacy into their classes [7]. Among these innovations, the flipped classroom is one of the teaching models applied by teachers and educators recently ( [8,9], January). e flipped classroom is a type of blended learning approach where the responsibility of learning goes back to learners [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Aristovnik et al 2020;Molnár et al 2020). Among the applied research methodologies, questionnaires appeared the most often, but we can also see examples of interviews (Piyatamrong et al 2021;Kálmán et al 2021), case studies (Molnár et al 2020), and interpretative phenomenological analysis (Kee 2021). Regarding educational levels, students' attitudes and experiences about online education were most measured in BA and postgraduate courses, and postgraduate students were found to be more prepared and successful in online education (Tang et al 2021).…”
Section: The Impact Of Covid-19 On Higher Educationmentioning
confidence: 99%
“…Regarding educational levels, students' attitudes and experiences about online education were most measured in BA and postgraduate courses, and postgraduate students were found to be more prepared and successful in online education (Tang et al 2021). Programs are also an important factor in terms of online education experience, as the replacement of traditional education with practical courses in engineering (Piyatamrong et al 2021) or medical programs (Amir et al 2020) requires a different approach. There are different results by gender in adoption of online education.…”
Section: The Impact Of Covid-19 On Higher Educationmentioning
confidence: 99%
“…En este aspecto, la educación superior enfrenta grandes desafíos a partir de la emergencia sanitaria y el distanciamiento social debido a la pandemia de la COVID 19 (Alvarez et al, 2021;Elgueta, 2020;García-Morales et al, 2021). Si se considera que una disrupción está relacionada a una rotura o una interrupción brusca, la educación disruptiva es aquella que pretende romper con lo establecido o las estructuras tradicionales para mejorar los procesos educativos en función de las características del actual contexto, basados en las nuevas tecnologías de información y de comunicación (Abdel-Basset et al, 2021;Molano, 2018;Piyatamrong et al, 2021).…”
Section: Introductionunclassified